Effects of MGA in receiving diets on health, performance, and carcass characteristics - Sulpizio, M.J.; Kessen, T.J.; Loe, E.R.; Montgomery, Sean P.; Pike, J.N.; Sindt, J.J.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A trial was conducted using 723 crossbred heifers (468 lb initially) to evaluate the effects of including melengestrol acetate (MGA) in receiving diets on growth performance, morbidity, mortality, and carcass characteristics. Treatments were: 1) MGA included in the receiving diet at a rate of 0.5 mg per heifer daily or 2) no MGA in the receiving diet. Diets were fed once daily and contained 42% steam-flaked corn, 45% alfalfa hay, 6% steep liquor, and 2% tallow; monensin and tylosin were included. Receiving diets were fed for 35 days. After 35 days MGA was fed to all heifers, and cattle were stepped up to common finishing diets. Cattle exhibiting clinical signs of bovine respiratory disease (BRD) were treated with Excenel (1 ml/100 lb body weight) for 3 days. Animals requiring followup treatment received the same therapy. Cattle pulled a third time received oxytetracycline (4.5 ml/100 lb body weight) and Predef (5 ml/heifer). Initial respiratory pulls (73.9% for MGA and 77.3% for no MGA), re-treatments, and death loss were not different (P>0.40) during the first 35 days. The number of heifers requiring a third antibiotic treatment tended (P=0.09) to be higher for heifers not receiving MGA. Average daily gain (deads out) for the first 35 days tended to be higher for heifers fed MGA (P=0.06), but dry matter intake and feed efficiency were not different between treatments (P>0.17). Gain throughout the 220-day feeding period was 2.6% higher for cattle fed MGA during the receiving phase (P=0.05). Overall, feed intake and feed efficiency were not different (P>0.50) between treatments, but heifers fed MGA during the initial receiving period tended to have heavier carcass weights (P=0.13). No differences were detected in quality grade, yield grade, or marbling (P>0.23). Feeding MGA during the initial 35 days after arrival may improve gain and carcass weights.
Keywords: Beef; MGA; Health; Performance; Carcass characteristics